Practising Integrative Medicine - The Star, Audrey Edwards (2008)
HOSPITALS can be scary places, even daunting Images of grim faced doctors and nurses in white coats overcrowded wards and long hours of waiting to be treated are just some that crowd the brain when the word hospital is mentioned.